Glossary of import management terms (ITC GenevaCH, 1995)
Covers the most commonly encountered terms in the different areas of import supply management as well as terms in shipping, insurance and materials management. Provides French, Portuguese and Spanish equivalents of the English terms covered in the glossary
DC